The Psychological Pleasure and Pain of Choosing When People Prefer Choosing at the Cost of Subsequent Outcome Satisfaction. [article]. - Botti, Simona
This empirical investigation tested the hypotesis that the benefits of personal choosing are restricted to choices made from among attractive alternatives. Findings from vignette and laboratory studies shows that contrary to people's self-predictions prior to to actually choosing, choosers only proved more satisfied than nonchoosers when selecting from among more preffered alternatives. When selecting from among less preffered alternatives, nonchoosers proved more satisfied with the decision outcome than choosers. Subsequent analyses revealed that differences in outcome satisfaction between choosers and nonchoosers emerge even before the decision outcome is experienced and that interventions during the decision-making process can serve to attenuate these differences. Theoretical and practical implications are discussed. -- (from the author)
Keywords: Psychology-Periodicals.